2006
DOI: 10.1890/0012-9658(2006)87[3029:eolsda]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Large-Scale Source–sink Dynamics and Long-Distance Dispersal Among Wood Thrush Populations

Abstract: Source-sink dynamics are commonly thought to occur among Wood Thrush (Hylocichla mustelina) and other songbird populations, allowing for the persistence of populations with negative growth rates ("sinks") through immigration from populations with positive growth rates ("sources"). Knowledge of source-sink dynamics is important for management and conservation because the removal of source habitat should result in the extinction of dependent sinks. However, since research has focused on identifying individual so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 31 publications
5
62
0
Order By: Relevance
“…3). Our results are consistent with recent observations that most boreal songbirds use home ranges far larger than their defended territories, that individuals respond to landscape-scale habitat, and that populations are synchronized on a scale of kilometers to tens of kilometers (Toms et al 2004, Betts et al 2006a, Taylor and Krawchuk 2006, Tittler et al 2006, Leonard 2007, Rempel 2007). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3). Our results are consistent with recent observations that most boreal songbirds use home ranges far larger than their defended territories, that individuals respond to landscape-scale habitat, and that populations are synchronized on a scale of kilometers to tens of kilometers (Toms et al 2004, Betts et al 2006a, Taylor and Krawchuk 2006, Tittler et al 2006, Leonard 2007, Rempel 2007). …”
Section: Discussionsupporting
confidence: 92%
“…Recent research has made it clear that regular landscape-scale extra-territorial movements are typical behavior for most forest songbird species, that nonterritorial "floaters" are common in some situations, and that the expression of both of these behaviors is often influenced by landscape structure (Norris and Stutchbury 2001, Fraser and Stutchbury 2004, Woolfenden et al 2005). All of these forms of movement can be affected by a species' population status and likely play an important role in synchronizing the dynamics of forest songbird populations on a scale of kilometers to tens of kilometers (Toms et al 2004, Tittler et al 2006. Consequently, consideration of patterns of space use will enhance interpretation of information on the demographics and resilience of local songbird populations.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, because adult birds are typically considered highly philopatric (e.g., Greenwood andHarvey 1982, Holmes and, natal dispersal distances will often determine distances between interacting sites of population sources and population sinks. A few previous studies have found correlations in the abundance of passerine birds from one year to the next in areas 2-100 km apart, which is evidence of source-sink dynamics at this spatial scale (Winkler et al 2005, Tittler et al 2006, McKim-Louder et al 2013). However, the geographic scales at which source-sink dynamics operate in avian ecology remain poorly understood.…”
Section: Discussionmentioning
confidence: 79%
“…These effects seem to be general. Evolution of dispersal strategies have major impacts on rate and mode of range-shifting (Dytham 2009), and variance in dispersal distance is critical in landscape-scale population connectivity and recolonisation (Trakhtenbrot et al 2005;Tittler et al 2006;van Houtan et al 2007).…”
Section: Identifying and Understanding Evolution Of Key Traits Associmentioning
confidence: 99%